Potential Prevalence of Front-of-Package Labels on Packaged Foods in a Supermarket Chain in the Northeast United States Under Two Proposed Labeling Systems - Joshua Petimar; C. Ross Hatton; Yutong Zhang; Alyssa J. Moran; Anna H. Grummon; Lauren P. Cleveland; Jason P. Block; Aviva A. Musicus (Journal of the Academy of Nutrition and Dietetics, 2026)

A quasi-differential measurement of neutron scattering from tantalum between 0.65 MeV and 20 MeV - Gregory J. Siemers; Yaron Danon; Sukhjinder Singh; Katelyn C. Keparutis; Peter J. Brain; Benjamin H. Wang; Adam M. Daskalakis; Devin P. Barry; Michael J. Rapp; Robert C. Block (Annals of Nuclear Energy, 2025)

Deep diving behaviour in oceanic manta rays and its potential function - Calvin S. Beale; Ferawati Runtuboy; Abraham B. Sianipar; Angela J. E. Beer; Kadarusman; Mark V. Erdmann; Edy Setyawan; Lydia Green; Clinton A. J. Duffy; Samantha Andrzejaczek; Barbara A. Block; Kerstin Forsberg; et al. (Frontiers in Marine Science, 2025)
Deep dives are performed by a range of marine megafauna, yet their function remains poorly understood. Proposed functions include foraging, predator avoidance, and navigation, but limited fine-scale data have hindered rigorous testing of these hypotheses. Here, depth time-series data from eight recovered and 16 non-recovered satellite tags deployed on oceanic manta rays ( Mobula birostris ) in Indonesia, Peru, and New Zealand were examined to characterise extreme dives and identify their potential function. From a total of 46,945 dives, 79 extreme dives (>500 m) were recorded, 11 of which were documented from recovered tags and associated high sampling frequency. Extreme dives were distinguished by rapid descents (up to 2.9 m s⁻¹), brief horizontal “steps” at depth, gradually slowing ascents, and extended periods spent near the surface both before and after diving. Unlike typical foraging dives, no substantial bottom phase was observed, and vertical oscillations—expected if feeding at depth—were absent. Extreme dives also occurred more frequently with increasing distance from the continental shelf edge as well as preceding periods of high 72h distance travelled, indicating they may inform subsequent movements. We propose that extreme dives enable oceanic manta rays to survey the properties of the water column, likely gathering environmental cues—such as temperature, dissolved oxygen, or geomagnetic gradients—to guide navigation and/or the decision to leave or remain in a general area. In open-ocean environments where external reference points are absent, such costly but infrequent dives may provide critical information for long-distance movements. Our results offer new insights into the role of extreme diving behaviour in oceanic manta rays and highlight the importance of fine-scale data for understanding deep-diving behaviours in marine megafauna.

Functional assessments of short-term spatial memory in the Dog Aging Project identify strong associations with age that are not moderated by body mass - Stephanie H. Hargrave; Amber J. Keyser; Emma Kristal; Gene E. Alexander; Theadora A. Block; Emily E. Bray; Laura E. L. C. Douglas; Brenda S. Kennedy; Daniel E. L. Promislow; David A. Raichlen; Dog Aging Project Consortium; Evan L. MacLean (GeroScience, 2025)

Discrete, recurrent, and scalable patterns in non-operant judgement underlie affective picture ratings - Leandros Stefanopoulos; Byoung-Woo Kim; John Sheppard; Emanuel A. Azcona; Nicole L. Vike; Sumra Bari; Shamal Lalvani; Sean Woodward; Nicos Maglaveras; Martin Block; Aggelos K. Katsaggelos; Hans C. Breiter (Cognitive Processing, 2025)
Operant keypress tasks in a reinforcement-reward framework where behavior is shaped by its consequence, show lawful relationships in human preference behavior (i.e., approach/avoidance) and have been analogized to “wanting”. However, they take 20–40 min as opposed to short non-operant rating tasks, which can be as short as 3 min and unsupervised, thus more readily applied to internet research. It is unknown if non-operant rating tasks where each action does not have a consequence, analogous to “liking”, show similar lawful relationships. We studied non-operant, picture-rating data from three independent population cohorts ( N = 501, 506, and 4019 participants) using the same 7 -point Likert scale for negative to positive preferences, and the same categories of images from the International Affective Picture System. Non-operant picture ratings were used to compute location, dispersion, and pattern (entropy) variables, that in turn produced similar value, limit, and trade-off functions to those reported for operant keypress tasks, all with individual R 2 > 0 . 80. For all three datasets, the individual functions were discrete in mathematical formulation. They were also recurrent or consistent across the cohorts and scaled between individual and group curves. Behavioral features such as risk aversion and other interpretable features of the graphs were also consistent across cohorts. Together, these observations argue for lawfulness in the modeling of the ratings. This picture rating task demonstrates a simple, quick, and low-cost framework for quantitatively assessing human preference without forced choice decisions, games of chance, or operant keypressing. This framework can be easily deployed on any digital device worldwide.

Unresolved resonance parameter evaluation and uncertainty quantification of n + 181Ta reactions - Jesse M. Brown; Devin P. Barry; Amanda Lewis; Timothy H. Trumbull; Marco T. Pigni; Travis Greene; Robert C. Block; Alec Golas; Yaron Danon (Annals of Nuclear Energy, 2025)

Infrared photometry and spectrometry of satellites and debris at UKIRT - Eric C. Pearce; Harrison Krantz; Adam Block; Deatrick L. Foster (Journal of Space Safety Engineering, 2024)

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Satellite tagging insights into the seasonal movements and behavior of Mediterranean spearfish (Tetrapturus belone, Istiophoridae) - Danilo Malara; Pietro Battaglia; Martin C. Arostegui; Jonathan J. Dale; Barbara A. Block; Camrin D. Braun; Massimo Brogna; Silvestro Greco; Teresa Romeo (Frontiers in Marine Science, 2024)
The Mediterranean spearfish ( Tetrapturus belone ) is a highly migratory predator, also exploited by commercial and recreational fisheries although its catches are poorly reported. The fishing pressure on this species is currently unknown because catch and landing data are fragmentary. Furthermore, more ecological information (e.g. migratory movements) is needed to establish eventual management measures, and ICCAT has not examined the population status yet. Understanding species migratory movements is crucial for addressing conservation challenges and supporting management decisions. In this study we investigated the migratory movements, seasonal patterns, vertical behavior, and thermal preference of T. belone , with the aim to improve information on its ecology and behavior. Overall, six individuals were tagged in the Strait of Messina and Tyrrhenian Sea with pop-up satellite tags and their movements were mainly restricted to the central Mediterranean. Utilization distributions derived from geolocation revealed an overall and seasonal importance of the Tyrrhenian Sea and Strait of Sicily, as well as variability in winter habitat use. While the fish exhibited similar depth preference, spending the majority of time at depths ≤ 10 m, we observed that the Mediterranean spearfish is also able to perform sporadic deep dives below 200 m. Vertical movement showed a bimodal pattern common in other billfish species, characterized by occupation of shallower, warmer waters during the night and deeper, cooler waters during the day. This research increases knowledge on the migration ecology and habitat preference of T. belone which is important for management of this understudied species.

Complement component C1q is an immunological rheostat that regulates Fc:Fc$$γ$$R interactions - Edward C. So; Hua Zhou; Ariana Greenwell; Erin E. Burch; Yaping Ji; Emmanuel Y. Mérigeon; Henrik S. Olsen; Søren M. Bentzen; David S. Block; Xiaoyu Zhang; Scott E. Strome (Immunogenetics, 2023)

Prion strains: shining new light on old concepts - Alyssa J. Block; Jason C. Bartz (Cell and Tissue Research, 2023)

Goat browse selectivity during conservation grazing in an invaded eastern oak-hickory forest - Wanderson Novais; Benjamin A. Wenner; Jeremy A. Block; Simon C. Power; Elizabeth Porteus; G. Matt Davies (Agroforestry Systems, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Zea mays Volatiles that Influence Oviposition and Feeding Behaviors of Spodoptera frugiperda - Jessica P. Yactayo-Chang; Jorrel Mendoza; Steven D. Willms; Caitlin C. Rering; John J. Beck; Anna K. Block (Journal of Chemical Ecology, 2021)

Ancillary data from animal-borne cameras as an ecological survey tool for marine communities - T. K. Chapple; D. Tickler; R. C. Roche; D. T. I. Bayley; A. C. Gleiss; P. E. Kanive; O. J. D. Jewell; S. J. Jorgensen; R. Schallert; A. B. Carlisle; J. Sannassy Pilly; S. Andrzejaczek; et al. (Marine Biology, 2021)
Underwater visual surveys represent an essential component of coastal marine research and play a crucial role in supporting the management of marine systems. However, logistical and financial considerations can limit the availability of survey data in some systems. While biologging camera tag devices are being attached to an increasing diversity of marine animals to collect behavioral information about the focal species, the ancillary imagery collected can also be used in analytical techniques developed for diver-based surveys. We illustrate this approach by extracting ancillary data from shark-borne camera tag deployments focused on the behavior of a White shark ( Carcharodon carcharias) off Gansbaai, South Africa, and a Grey Reef shark ( Carcharhinus amblyrhynchos) within the Chagos Archipelago. Within the giant kelp forest environment of Gansbaai we could determine the spatial density of kelp thali and underlying substrate composition. Within the coral reef environment, the animal-borne video allowed us to determine the approximate percent and type of benthic cover, as well as growth form and genus of corals down to the upper mesophotic zone. We also enumerated fish species-level abundance over reef flat and wall environments. We used established dive-survey methods to analyze video data and found the results to be broadly comparable in the two systems studied. Our work illustrates the broad applicability of ancillary animal-borne video data, which is analogous in type and quality to diver-based video data, for analysis in established marine community survey frameworks. As camera tags and associated biologging technologies continue to develop and are adapted to new environments, utilising these data could have wide-ranging applications and could maximise the overall cost–benefit ratio within biologging deployments.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Assessment of an anti-scale low-frequency electromagnetic field device on drinking water biofilms - F. Gosselin; L. Mathieu; J.-C. Block; C. Carteret; H. Muhr; F. P. A. Jorand (Biofouling, 2018)

Complex layering of the Orange Mountain Basalt: New Jersey, USA - John H. Puffer; Karin A. Block; Jeffrey C. Steiner; Chris Laskowich (Bulletin of Volcanology, 2018)

Influence of temperature and oxygen on the distribution of blue marlin ( Makaira nigricans ) in the Central Pacific - Aaron B. Carlisle; Randall E. Kochevar; Martin C. Arostegui; James E. Ganong; Michael Castleton; Jason Schratwieser; Barbara A. Block (Fisheries Oceanography, 2017)
The blue marlin ( Makaira nigricans ) is a highly migratory pelagic predator of tropical and subtropical seas. Information on the habitat use of marine species is fundamental to understanding their ecology and population dynamics and is needed to inform responsible management strategies. Using a long‐term satellite tagging data set from The International Game Fish Association Great Marlin Race, we examined habitat use and how oxygen and temperature influence the horizontal and vertical distributions of blue marlin in the Central Pacific. Blue marlin primarily occurred in warm waters (26–30°C) and exhibited a diel bimodal depth distribution across the 5‐year data record (2009–2013), with fish spending the majority of their time near the surface at night and at deeper depths during the day (25–100 m). The depth distribution of blue marlin was limited in areas where low oxygen and/or temperature conditions occur closer to the surface, with the extent of habitat compression being greatest when both oxygen and temperature were limiting. The migrations of blue marlin appeared restricted during the 2010 La Niña, when increased equatorial upwelling resulted in an extension of the cold, low oxygen waters of the cold tongue into the Central Pacific, creating a barrier to the trans‐equatorial migrations that occurred during all other tagging years. If the frequency and intensity of La Niña events increases and the oxygen minimum layer continues to expand as has been predicted under certain climate change scenarios, the migratory behavior and habitat availability of blue marlin may be impacted.

Life in the open ocean: seasonal migration and diel diving behaviour of Southern Hemisphere porbeagle sharks (Lamna nasus) - Malcolm P. Francis; John C. Holdsworth; Barbara A. Block (Marine Biology, 2015)

Genetic variants in the folate pathway and risk of childhood acute lymphoblastic leukemia - Catherine Metayer; Ghislaine Scélo; Anand P. Chokkalingam; Lisa F. Barcellos; Melinda C. Aldrich; Jeffrey S. Chang; Neela Guha; Kevin Y. Urayama; Helen M. Hansen; Gladys Block; Vincent Kiley; John K. Wiencke; et al. (Cancer Causes & Control, 2011)

Heterologous hybridization to a complementary DNA microarray reveals the effect of thermal acclimation in the endothermic bluefin tuna ( Thunnus orientalis ) - PEDRO C. CASTILHO; BRADLEY A. BUCKLEY; GEORGE SOMERO; BARBARA A. BLOCK (Molecular Ecology, 2009)
The temperature stress that pelagic fishes experience can induce physiological and behavioural changes that leave a signature in gene expression profiles. We used a functional genomics approach to identify genes that were up‐ or down‐regulated following thermal stress in the Pacific bluefin tuna. Following the acclimation period, 113, 81 and 196 genes were found to be differentially expressed between the control (20 °C) and cold (15°) treatment groups, in ventricle, red muscle and white muscle, respectively. The genes whose expression levels were responsive to thermal acclimation varied according to muscle fibre type, perhaps reflecting the tissue‐specific degrees of endothermy characteristic of this species.

Habitat and behaviour of yellowfin tuna Thunnus albacares in the Gulf of Mexico determined using pop‐up satellite archival tags - K. C. Weng; M. J. W. Stokesbury; A. M. Boustany; A. C. Seitz; S. L. H. Teo; S. K. Miller; B. A. Block (Journal of Fish Biology, 2009)
This study presents the first data on movement, habitat use and behaviour for yellowfin tuna Thunnus albacares in the Atlantic Basin. Six individuals were tracked in the Gulf of Mexico using pop‐up satellite archival tags. Records up to 80 days in length were obtained, providing information on depth and temperature preferences as well as horizontal movements. Thunnus albacares in the Gulf of Mexico showed a strong preference for the mixed layer and thermocline, consistent with findings for this species in other ocean basins. Fish showed a diel pattern in depth distribution, remaining in surface and mixed layer waters at night and diving to deeper waters during the day. The vertical extent of T. albacares habitat appeared to be temperature limited, with fish generally avoiding waters that were >6° C cooler than surface waters. The vertical and thermal habitat usage of T. albacares differs from that of bigeye Thunnus obesus and bluefin Thunnus thynnus , Thunnus orientalis and Thunnus maccoyii tunas. These results are consistent with the results of earlier studies conducted on T. albacares in other oceans.

Near real time satellite tracking of striped marlin (Kajikia audax) movements in the Pacific Ocean - John C. Holdsworth; Tim J. Sippel; Barbara A. Block (Marine Biology, 2009)

Culture-based methods for detection and identification of Streptococcus agalactiae in pregnant women—what are we missing? - A. Adler; C. Block; D. Engelstein; D. Hochner-Celnikcier; R. Drai-Hassid; A. E. Moses (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Water management in the Flemish steel industry: the Arcelor Gent case - R. Mortier; C. Block; C. Vandecasteele (Clean Technologies and Environmental Policy, 2007)

Migration and habitat of white sharks (Carcharodon carcharias) in the eastern Pacific Ocean - Kevin C. Weng; Andre M. Boustany; Peter Pyle; Scot D. Anderson; Adam Brown; Barbara A. Block (Marine Biology, 2007)

Striped marlin ( Tetrapturus audax ) movements and habitat utilization during a summer and autumn in the Southwest Pacific Ocean - TIM J. SIPPEL; PETER S. DAVIE; JOHN C. HOLDSWORTH; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Six striped marlin ( Tetrapturus audax ) were caught on hook and line from recreational fishing boats near northern New Zealand (34°S, 174°E) and tagged and released with pop‐off satellite archival tags. For periods ranging from 22 to 60 days over the geographical range 168°E–170°W and 13–34°S, five tags collected a total of 202 days (range of 21–60 days) of data. These data permit the investigation of striped marlin geographical and vertical movements and water temperatures occupied from February to June 2003. One hundred and one days of geoposition data showed a preliminary view of their movements in and around New Zealand waters. Transmitted temperature and depth data indicated striped marlin spent 80% (±2%) of their time in the mixed layer including 72% (±2%) of their time in the top 5 m. Temperature data indicated 75% (±10%) of the striped marlin’s time was spent in water temperatures between 20.1 and 24.0°C. Tagged striped marlin moved faster during periods of directed movement away from New Zealand versus periods of passive movements when the fish were proximal to New Zealand or not moving in any specific direction. These data support some existing hypotheses about striped marlin physiological ecology and allow preliminary suggestions about how striped marlin bycatch might be reduced.

Annual migrations, diving behavior, and thermal biology of Atlantic bluefin tuna, Thunnus thynnus, on their Gulf of Mexico breeding grounds - Steven L. H. Teo; Andre Boustany; Heidi Dewar; Michael J. W. Stokesbury; Kevin C. Weng; Shana Beemer; Andrew C. Seitz; Charles J. Farwell; Eric D. Prince; Barbara A. Block (Marine Biology, 2007)

A Review of Fine Root Dynamics in Populus Plantations - R. M. A. Block; K. C. J. Van Rees; J. D. Knight (Agroforestry Systems, 2006)

Characterization of Aspen ASH, Sand and Log-Yard Waste Mixtures from an Aspen-Based Oriented Strand Board Mill for Use as an Intermediate Landfill Cover - R. M. A. Block; K. C. J. van Rees (Water, Air, & Soil Pollution, 2004)

Effects of Fipronil and Chlorpyrifos on Endocrine-Related Endpoints in Female Grass Shrimp (Palaemonetes pugio) - D. C. Volz; E. F. Wirth; M. H. Fulton; G. I. Scott; E. Strozier; D. S. Block; J. L. Ferry; S. S. Walse; G. T. Chandler (Bulletin of Environmental Contamination and Toxicology, 2003)

Cluster of Neonatal Infections in Jerusalem due to Unusual Biochemical Variant of Enterobacter sakazakii - C. Block; O. Peleg; N. Minster; B. Bar-Oz; A. Simhon; I. Arad; M. Shapiro (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Behaviour of a sharptail mola in the Gulf of Mexico - A. C. Seitz; K. C. Weng; A. M. Boustany; B. A. Block (Journal of Fish Biology, 2002)
A sharptail mola Masturus lanceolatus was tagged and released with a pop‐up satellite archival tag in the Gulf of Mexico and tracked for 61 days. The fish travelled a horizontal distance of 594 km while generally staying in water 20° C. Occasionally the sharptail mola dived to depths >700 m and experienced water colder than 6° C.

Increasing Incidence of Gonorrhea in Israel Associated with Countrywide Dissemination of a Ciprofloxacin-Resistant Strain - Yagupsky P.; Schahar A.; Peled N.; Porat N.; Trefler R.; Dan M.; Keness Y.; Block C. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Planetary habitability: is Earth commonplace in the Milky Way? - S. Franck; A. Block; W. Bloh; C. Bounama; I. Garrido; H.-J. Schellnhuber (The Science of Nature, 2001)

Depth and muscle temperature of Pacific bluefin tuna examined with acoustic and pop-up satellite archival tags - David J. Marcinek; Susanna B. Blackwell; Heidi Dewar; Ellen V. Freund; Charles Farwell; Daniel Dau; Andrew C. Seitz; Barbara A. Block (Marine Biology, 2001)

Structure and migration corridors in Pacific populations of the Swordfish Xiphius gladius , as inferred through analyses of mitochondrial DNA - C. A. Reeb; L. Arcangeli; B. A. Block (Marine Biology, 2000)

Factors Associated with Nosocomial Diarrhea and Clostridium difficile -Associated Disease on the Adult Wards of an Urban Tertiary Care Hospital - M. J. Schwaber; A. Simhon; C. Block; V. Roval; N. Ferderber; M. Shapiro (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Outbreak of Bloodstream Infections Associated with Dialysis Machine Waste Ports in a Hemodialysis Facility - C. Block; R. Backenroth; E. Gershon; R. Israeli; A. Simhon; M. Popovtzer; M. Shapiro (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Forestry Education: Adapting to the Changing Demands on Professionals - V. Alaric Sample; Paul C. Ringgold; Nadine E. Block; James W. Giltmier (Journal of Forestry, 1999)
Recent evolution in the practice of forestry can be linked to changes in the public's perception of sustainability and to developments in science, communications, and global markets. In response, when hiring graduates of professional forestry programs, forestry employers have changed the set of skills and competencies sought. A nationwide survey of forestry employers, educators, and recent graduates, conducted to assess how well US forestry programs are preparing professionals to practice forestry today, reveals some discrepancies between what employers want and what the schools provide. External financial and political pressures on higher education make it difficult for educators to close these gaps, but opportunities exist for employers to help.

Horizontal movements and depth distribution of large adult yellowfin tuna ( Thunnus albacares ) near the Hawaiian Islands, recorded using ultrasonic telemetry: implications for the physiological ecology of pelagic fishes - R. W. Brill; B. A. Block; C. H. Boggs; K. A. Bigelow; E. V. Freund; D. J. Marcinek (Marine Biology, 1999)

Failure of Mass Antibiotic Prophylaxis to Control a Prolonged Outbreak of Meningococcal Disease in an Israeli Village - S. Shehab; N. Keller; A. Barkay; L. Leitner; A. Leventhal; C. Block (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Motor learning in the "podokinetic" system and its role in spatial orientation during locomotion - K. D. Weber; W. A. Fletcher; C. R. Gordon; G. Melvill Jones; E. W. Block (Experimental Brain Research, 1998)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)

Bacterial influence on partitioning rate during the biodegradation of styrene in a biphasic aqueous-organic system - P. Osswald; P. Baveye; J. C. Block (Biodegradation, 1996)